Do Cumulative Revision Rate and First-time Re-revision Rate Vary Between Short and Standard Femoral Stem Lengths? A Multinational Registry Study - Rilby, Karin ; 0000-0003-0185-5249; Van Veghel, Mirthe H.W.; Mohaddes, Maziar; Van Steenbergen, Liza N.; Lewis, Peter L.; Kärrholm, Johan; Schreurs, Berend W.; Hannink, Gerjon (Clinical Orthopaedics and Related Research, 2025)
Background Advocates of short-stem THA suggest that these devices preserve proximal femoral bone for future revisions. This contention is as yet unsupported by robust evidence, and ultimately, it will be irrelevant if short-stem THA increases the overall risk of premature revision. To our knowledge, large, registry-based efforts have yet to explore the types of stems used in first-time stem revision as well as the survivorship of short versus standard-length femoral stems in THA. Questions/purposes (1) Which stems are used in the first stem revision of primary short-stem and standard-stem THAs? (2) What is the overall cumulative revision rate (CRR) of primary short-stem THAs compared with primary standard-stem THAs? (3) What is the overall cumulative re-revision rate of primary short-stem THAs compared with primary standard-stem THAs? Methods Patients with short-stem THAs, defined as a short stem with mainly metaphyseal fixation, registered in the Australian Orthopaedic Association National Joint Replacement Register (AOANJRR), the Dutch Arthroplasty Register (Landelijke Registratie Orthopedische Interventies [LROI]), or the Swedish Arthroplasty Register (SAR) between January 2007 and December 2022 were included (n = 15,771), as well as a propensity score-matched cohort (1:2) with standard-stem THAs, defined as a stem with a standard length (n = 31,542). Groups were matched on sex, age, year of procedure, diagnosis, bearing material, and surgical approach. After matching, the groups did not differ in terms of age (mean ± SD 63 ± 11 versus 64 ± 11 years), sex (48% [7546 of 15,771] male versus 48% [15,093 of 31,542] male), and diagnosis (93% [14,655 of 15,771] osteoarthritis [OA] versus 94% [29,585 of 31,542] OA). We used those three registries because all are high-quality national arthroplasty registries with high levels of completeness. Also, the AOANJRR is the only registry globally that reports on short-stem THA as its own entity. The type of stem used in revision surgery was classified as standard stem (< 160 mm) or long stem (≥ 160 mm). Overall CRR of primary THAs at 12 years of follow-up and overall CRR of all first-time revisions at 5 years were calculated using Kaplan-Meier survival analyses. Any type of revision was used as endpoint. Results In first-time stem revisions of the short-stem THAs, a standard stem was used more often (58% [116 of 201]) than in the revision of standard-stem THAs (46% [149 of 322]; p = 0.01). The 12-year overall CRRs between primary short-stem and standard-stem THAs did not differ (4.7% [95% confidence interval (CI) 4.0% to 5.5%] versus 5.1% [95% CI 4.5% to 5.7%], respectively; p = 0.20). The overall CRR for a second revision at 5 years also did not differ when primary short-stem THAs were compared with standard-stem THAs (20.9% [95% CI 16.8% to 25.8%]) versus 20.4% [95% CI 17.3% to 23.9%]; p = 0.80). Conclusion In light of these findings, there may be a perceived benefit of using short stems in primary THA if a revision is later required, as the short stems included in this study were to a higher degree revised using a standard (more bone-sparing) stem. Further, the first and second overall CRR of the studied short-stem THAs did not differ from that of standard-stem THAs, also supporting use of short-stem THA. Further research, preferably multinational registry-based studies, should be performed to confirm our findings.